2020
DOI: 10.48550/arxiv.2003.02144
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Online metric algorithms with untrusted predictions

Abstract: Machine-learned predictors, although achieving very good results for inputs resembling training data, cannot possibly provide perfect predictions in all situations. Still, decisionmaking systems that are based on such predictors need not only to benefit from good predictions but also to achieve a decent performance when the predictions are inadequate. In this paper, we propose a prediction setup for arbitrary metrical task systems (MTS) (e.g., caching, k-server and convex body chasing) and online matching on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…And interestingly, this value is a function of m, as the number of subsets, and θ = 2, as the algorithm proposed in [31] is a suboptimal algorithm. This is indeed our observation in Figure 4, where the degradation factor for m = 10 5 with θ = [2,3] is less than 1. This shows that the original algorithm proposed in [31] is not using the worst-case optimized parameter and one can find the worst-case optimized parameter θ by minimizing Eq.…”
Section: F Regret Analysis Of Data-driven Algorithm Design For One-wa...supporting
confidence: 85%
See 2 more Smart Citations
“…And interestingly, this value is a function of m, as the number of subsets, and θ = 2, as the algorithm proposed in [31] is a suboptimal algorithm. This is indeed our observation in Figure 4, where the degradation factor for m = 10 5 with θ = [2,3] is less than 1. This shows that the original algorithm proposed in [31] is not using the worst-case optimized parameter and one can find the worst-case optimized parameter θ by minimizing Eq.…”
Section: F Regret Analysis Of Data-driven Algorithm Design For One-wa...supporting
confidence: 85%
“…An important open question is how to achieve the "best-of-bothworlds", both near-optimal performance in typical settings, which requires data-driven adaptation, and a near-optimal competitive ratio. Toward this goal, there have been substantial efforts to improve the performance of competitive algorithms using predictions [1,2,3], ML advice [4,5,6,7], and advice from multiple experts [8]. In these approaches the goal is to allow online algorithms to use (potentially noisy) predictions (or advice) about future inputs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remark The independent, concurrent work of Antoniadas et al [2] has slight overlap with ours. In particular, they also showed that the PRP prediction model does not provide asymptotic benefits for randomized algorithms.…”
Section: Related Worksupporting
confidence: 66%
“…Closest to our work are the recent papers of Antoniadis et al (2020) and Rutten et al (2022). The former considers the problem of designing algorithms for metrical task systems (MTS) with blackbox advice.…”
Section: Online Algorithms With Black-box Advicementioning
confidence: 99%